The Effect of Si Oto Video on the Level of Knowledge of Traditional Medicine in Dempel Hamlet, Dokoro Village, Wirosari Sub-District, Grobogan - Eleonora Maryeta Toyo; Agustin Siti Solechah; Sri Suwani (Journal of World Future Medicine, Health and Nursing, 2024)
Video is a collection of images in a frame that is projected through a projector with a certain mechanism so as to produce images that appear to move. The purpose of this study was to determine the effect of SI OTO video on the level of knowledge of traditional medicine in Dempel Hamlet, Dokoro Village, Wirosari Grobogan District. The chosen research approach involves quantitative methodology, specifically employing an experimental design known as the one-group pretest-posttest without control design. This method is utilized to assess the impact of an intervention on the experimental group. The population and sample in this study were residents of Dempel Hamlet, Dokoro Village, Wirosari Subdistrict, Grobogan with a sample size of 276 people using purposive sampling technique. The collection was done by distributing knowledge questionnaires about traditional medicine. Data analysis used is univariate analysis and using Wilcoxon test. The results of descriptive statistics explained the mean value of the pretest was 1.92 and the mean value of the posttest was 2.73. This shows an increase in scores from pretest to posttest. The results of the Wilcoxon test show that the significance value is < 0.05, meaning that there is a significant difference in pretest and posttest scores in knowing the effect of the SI OTO video on the level of knowledge of traditional medicine in Dempel Hamlet, Dokoro Village, Wirosari Grobogan District.